Designing Financial Information Systems And Customer Management On Website-Based CCPA And P3A - Rafael Anthonio Nanda; Erdhi Widyarto Nugroho; Alexandra Adriani Widjaja (Journal of Business and Technology, 2022)
Business competition that is increasingly fierce in this era, requires companies to not only focus on profits but also focus on the needs of consumers and stakeholders. Along with the development of information technology, the company's efforts in meeting the needs of consumers and stakeholders, can be supported with the help of information systems. With the help of a well-integrated information system, companies can collect, process, analyze and store data more quickly, precisely and accurately and can maximize marketing, sales and service efforts to consumers. In CCPA and P3A, the recording of transactions and customer data is still done manually. Because of this, a financial information system and customer management were developed. Based on the results of the functionality test and the results of interviews with users, it proves that the system developed can support the performance of CCPA and P3A in terms of recording transaction data and customer data.